Alumni perceptions of the McNair scholars program at Kansas universities - Greene, Kathleen Veronica (Kansas State University, 2007)
This study investigated the strengths and weaknesses of the McNair program at the three Kansas Regents institutions. The population included 259 former McNair program participants from Kansas State University (KSU), the University of Kansas (KU), and Wichita State University (WSU) who graduated with baccalaureate degrees between 1996 and 2004. These alumni were asked to complete a two- part survey. Part one collected data on McNair alumni perceptions of the strengths and weaknesses of the program on a thirty-three item, five-point Likert scale. Additionally, part one collected data on McNair alumni recommendations regarding the amount of emphasis that should be placed on program services and activities. Next, part two collected selected demographics. This provided useful data to examine how selected demographics relate to program perceptions. One hundred and thirty-seven of the 259 McNair alumni completed the survey. Overall, the results of the data suggested that they perceived the services and activities to be more of a strength than a weakness. Also, the recorded comments by the alumni indicated that their experiences as McNair scholars were positive. McNair scholar alumni recommended providing more assistance with how to interview prospective faculty mentors, obtain financial assistance, and stay abreast of resources that would increase the number of McNair scholars enrolling in graduate school and completing a graduate degree. Further study is recommended to survey McNair alumni who have completed doctoral degrees regarding the need for services that would help strengthen areas that were perceived to be weaker than others. These areas include “Enrollment in a Graduate School Program Leading to a Doctorate Degree” and “Selecting and Working With a Faculty Mentor”. Additionally, further study is recommended to investigate how alumni differ in their perceptions of the strengths and weaknesses of the McNair Program by major field of study.
Keywords: Low-income; First-generation college students; Minority students; Graduate School; Education, General (0515)